Thermodynamic Functions of Chromatographic Retention of Sodium 2-((4-Amino-5- (thiophen-2-ylmethyl)-4h-1,2,4-triazol-3-yl)thio)acetate and its Impurities - Usenko, D. L.; Varynskyi, B. O.; Kaplaushenko, A. H.; Усенко, Дмитро Леонідович; Варинський, Борис Олександрович; Каплаушенко, Андрій Григорович (My University, 2023)
The aim of this work was to study the dependence of liquid chromatography retention on temperature and thermodynamic characteristics of the transfer of sodium 2-((4-amino-5-thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio) acetate, 2-(thiophen-2-)yl)acetohydrazide and 4-amino-5-(thiophen-2- ylmethyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione from the mobile phase to the stationary. HPLC system Agilent 1260 Infinity. Column Zorbax SBC18; 30 mm x 4.6 mm; 1.8 μm. The mobile phase consisted of water (0,1% HCOOH) and acetonitrile (0,1% HCOOH) (75:25). Flow rate is 0.4 mL/ min. The solutions of each substance were chromatographed at different temperatures from 30оС to 70оС with step 5оС. The sodium 2-((4-amino-5- thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate and its technological impurities are characterized by negative values of the enthalpy of transfer from the mobile phase to the stationary, so the process of transition of the substances from the mobile phase to the stationary prevails over the reverse process. The entropic term more than enthalpic term for the 2-(thiophene- 2-yl)acetohydrazide at the influence on retention.
Keywords: 1,2,4-triazoles; active pharmaceutical ingredient; HPLC; enthalpy; entropy